The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1182/blood-2013-10-532374
|View full text |Cite
|
Sign up to set email alerts
|

Implications of the miR-10 family in chemotherapy response of NPM1-mutated AML

Abstract: • High miR-10 family expression levels in AML patients are associated with achieving complete remission to induction chemotherapy.• Functional experiments did not show any impact of miR10a-5p in AML blast growth or survival at baseline conditions or after chemotherapy.Nucleophosmin-mutated acute myeloid leukemia (NPM1mut-AML) patients have a high rate of complete remission (CR) to induction chemotherapy. However, the mechanisms responsible for such effects are unknown. Because miR-10 family members are express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 15 publications
4
31
0
Order By: Relevance
“…Higher levels of miR10a-5p expression in AML compared to normal control and down-regulation of miR-10a-5p expression in CML patients with respect to healthy donor [27] implicated that miR-10a-5p may play a crucial role in mediating the differentiation of myeloid lineage. Previous report showed that no differences in CD11b or cell morphology were observed up to 72 h after miR-10a-5p overexpression in Kasumi-1 cells [30]. However, to date, minimal evidence exists to indicate that microRNAs which were involved in the differentiation block of M1 blasts and consequently monocytic differentiation differentially expressed between the M1 and M5 French-American-British (FAB) subtypes [31,32].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Higher levels of miR10a-5p expression in AML compared to normal control and down-regulation of miR-10a-5p expression in CML patients with respect to healthy donor [27] implicated that miR-10a-5p may play a crucial role in mediating the differentiation of myeloid lineage. Previous report showed that no differences in CD11b or cell morphology were observed up to 72 h after miR-10a-5p overexpression in Kasumi-1 cells [30]. However, to date, minimal evidence exists to indicate that microRNAs which were involved in the differentiation block of M1 blasts and consequently monocytic differentiation differentially expressed between the M1 and M5 French-American-British (FAB) subtypes [31,32].…”
Section: Discussionmentioning
confidence: 95%
“…Previous published research has highlighted that miR-10a-5p was significantly markedly overexpressed and influenced the chemotherapy response in NPM1 mut AML, which may exert its biological properties in AML by interfering with the p53 machinery, which is partly regulated by MDM4 [13,14,30]. Certain research suggested that nuclear factor-κB (NF-κB) p65 activated miR-10a-5p expression by directly combining miR-10a-5p promoter region in human breast cancer and colorectal cancer cell lines [37].…”
Section: Discussionmentioning
confidence: 99%
“…[60] High expression level of miR-10 family is associated with AML with mutated NPM-1. [25,61] Furthermore, miR-424 in AML patients with NPM-1 mutation was down-modulated. [62] In AML patients with the FLT3-ITD mutation, miR-451 and miR-144 were down-regulated while miR-155 was overexpressed.…”
Section: Micrornas' Significance In Extramedullary Amlmentioning
confidence: 98%
“…miRNAs therefore represent a new set of particularly attractive therapeutic targets in overcoming MDR in hematological malignancies. In addition, differential miRNA Blood Reviews 29 (2015) [33][34][35][36][37][38][39][40][41][42][43][44] expression profiles in serum or plasma samples can be used as noninvasive diagnostic or prognostic biomarkers. Studies on miRNAs have therefore quickly moved from research on the molecular basis of cancer to clinical applications.…”
Section: Introductionmentioning
confidence: 99%